Teorija komunikacijskega tujejezičnega izobraževanja - Frank, Meta (Vestnik za tuje jezike, 2014)
The paper presents the theoretical starting points of the theory of communicative foreign language education developed by a Russian educator and didactician E. I. Passov and presented in a monograph entitled Urok inostrannogo jazyka. The article describes the aspects of foreign language education (cognition, development, learning and training), methodical content of a foreign language lesson and elements of the "logic" of foreign language classes which teachers should take into account in order to effectively encourage the language abilities of students.
Keywords: Passov, Efim Izrailevič; tuji jeziki; jezikovni pouk; tujejezična kultura; učne ure; komunikacijska situacija; govorno-miselne naloge; sporazumevalna zmožnost